Strategi Guru Pendidikan Agama Islam DalamMeningkatkan Keterampilan Berpikir Kritis Siswa SD Muhammadiyah Perumnas - Sulfiadi; Ferdinan; Abd. Rahman B (Advances In Education Journal, 2025)
This study aims to examine the implementation of the Cooperative Learning model of the Jigsaw type in the Islamic Cultural History subject to improve the learning outcomes of tenth-grade students at Madrasah Aliyah Syekh Yusuf Gowa. The research employed Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. Data collection techniques included learning outcome tests, student activity observations, and documentation. The data were analyzed quantitatively using descriptive statistics to assess the percentage increase in learning outcomes. A comparison between the pre-cycle, Cycle I, and Cycle II results showed a significant improvement in student learning outcomes. In the pre-cycle, only 8 out of 26 students (31%) achieved mastery, while 18 students (69%) did not. In Cycle I, 17 students (66%) achieved mastery, with 9 students (34%) still below the standard. By Cycle II, the number of students meeting the minimum passing grade (KKM) increased to 23 (89%), with only 3 students (11%) remaining below the standard. In each cycle, students who did not reach mastery were given enrichment activities in the form of Qur’an memorization to help improve their scores and meet the KKM.